Review of pathological findings in laparoscopic sleeve gastrectomy specimens performed for morbid obesity. Issue 10 (26th June 2020) - Nowak, Klaudia; DiPalma, Adam; Serra, Stefano; Quereshy, Fayez; Jackson, Timothy; Okrainec, Allan; Chetty, Runjan
Abstract : Background: Bariatric surgical procedures are employed when there is a failure of lifestyle modification in arresting obesity. Laparoscopic sleeve gastrectomy (LSG) is quickly becoming the bariatric surgical procedure of choice. LSG results in a gastric remnant that is subject to pathological examination. The objective of this paper is to review the literature in regard to histological findings identified in gastric remnants post-LSG and identify the most pertinent histological findings. Materials and methods: A literature search was performed to identify relevant case series. Data gathered from relevant case series then underwent statistical analysis. Results: The most common histological findings in an LSG specimen were clinically indolent findings such as no pathological abnormalities identified followed by non-specific gastritis. A minority of cases demonstrated clinically actionable findings for which Helicobacter pylori represented the majority of these findings. Conclusion: There is a broad spectrum of pathological findings in LSG specimens, ranging from clinically indolent to clinically actionable. The most common histological findings are clinically indolent and only a small portion are of clinical significance and, hence, actionable.